OPTIMALISASI METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN TEMATIK UNTUK MENGEMBANGKAN POLA PIKIR KRITIS SISWA DI KELURAHAN SURALAYA KECAMATAN PULOMERAK, KOTA CILEGON - Tabroni, Tabroni; Wicaksono, Dityo Bagas; Purwanti, Divia Yuni; Baidillah, Nazwa; Ramadhania, Marsya Diva (Yayasan Education and Social Center, 2025)
This community service activity aims to optimize the application of Problem Based Learning (PBL) in thematic learning to develop students’ critical thinking skills in Suralaya Village, Pulomerak District, Cilegon City. The program was implemented in four educational institutions: SD Pringori, SMPN 10 Cilegon, SMA Negeri 4 Cilegon, and MDTA Al-Latif. The methods included teacher training, classroom observation, PBL implementation mentoring, and student-teacher reflection. The results showed that PBL encouraged students to become active learning agents, enhanced their critical thinking abilities, and strengthened collaboration between schools and the social environment. Furthermore, there was a transformation in the teacher’s role into that of a learning facilitator. The implication of this activity suggests that PBL is a relevant approach to improve learning quality in local educational contexts, particularly in fostering character development and higher-order thinking skills.